Quasi-hydrostatic Limit of LiF as a Pressure Transmitting Medium and Its Equation of States - 郭家增 吴也 朱峰 巫翔 杨科 秦善 (Chinese physics letters, 2014)
Quasihydrostatic limit of LiF as a pressure transmitting medium is investigated by synchrotron radiation x-ray diffraction combined with the diamond anvil cells technique up to 60 GPa at room temperature. The equation-of- state parameters of LiF are determined to be Vo = 65.7（2）A3 Bo = 58（3） GPa and B＇0 = 4.9（2） in the silicon oil environment; Vo = 67.4（3） A3, Bo = 51（3） GPa and B＇0 = 4.7（2） without pressure transmitting medium. The full width at half maximum of LiF （111） peak increases with the increase of pressure in two independent experiments. The pressure distribution in the sample chamber is estimated by line-scanning x-ray diffraction measurements across the chamber＇s center, which presents as homogeneous with Pmax - Pmin Of about 1 GPa below 40 GPa.